PENGARUH BIAYA MAKANAN, BIAYA MINUMAN, DAN BIAYA BANQUET TERHADAP LABA DI HARRIS HOTEL KELAPA GADING - Pamuji Gesang Raharjo; Lutfi Suyudi (LPPM Universitas Asa Indonesia, 2018)
The purpose of this study was to determine the cost of food, beverage costs and banquet costs to earnings at HARRIS Kelapa Gading Hotel. The research used by the author uses secondary data obtained by the author of HARRIS Kelapa Gading Hotel for 3 years, namely from 2015-2017. Data analysis that can be used is multiple linear regression, which in conducting multiple linear regression analysis must go through a classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. While the Hypothesis test used is F Test, T Test, and Determination Correlation Test (R2). From the results we can see greater than the Cost, Beverage Cost and Cost for Securities at HARRISKelapa Gading Hotels both online and simultaneously (simultaneously).